Pengaruh Pembangunan Perumahan Bagi Rumah Tangga Miskin (RTM) Terhadap Kondisi Sosial-Ekonomi Masyarakat Kelurahan Sawah Besar, Kecamatan Gayamsari, Kota Semarang - Hapsari, Maharani Tri (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
This research is motivated by the problems there is the number of poor people in Central Java who live in the houses not livable. Therefore, Central Java Provincial Government made a Housing Development Program for Poor Households. Central Java province has been conducting monitoring and evaluation of the program, but is only the aspect of a physicaly output, whereas according to the concept Tridaya that housing construction should also touching the social and economic conditions of society, so the researchers are interested in conduct research on how the influence of the development program of housing for poor households to the socio-economic condition of society in Kelurahan Sawah Besar, Kecamatan Gayamsari Kota Semarang. The research methodology used in this study is a mixture of qualitative and quantitative descriptive analysis with nonparametric statistical methods using statistical test of Wilcoxon different test as well as the influence of the Pearson correlation test using SPSS version 20. The conclusion is the average percentage of target accuracy analysis is based on the condition of households amounted to 31.50%, while the results of the analysis target accuracy of the condition of the house building is at 68.75 %. As a result of the implementation of the program is able to improve the physical condition by 55%, improving social conditions by 45%, but the economic outlook has decreased by 10%, due to a decrease in variable levels of spending, which is caused by the number of respondents who went into debt in the implementation of development / repair their house. Therefore, the need for revisions or changes in the criteria determining the target households, using of local wisdom, which is expected to generate empowerment in its implementation so as to avoid people from debt problems.